THE IMPACT OF EMPLOYING INTERACTIVE WORDWALL MEDIA AND THE TGT (TEAMS GAMES TOURNAMENT) COOPERATIVE LEARNING MODEL ON RAISING STUDENT MOTIVATION AND LEARNING OUTCOMES ON THE REACTION RATE MATERIAL - Ginting, Ela Riana Br (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The purpose of this study was to determine learning achievement, learning motivation, and the relationship between the two. This study was conducted at Santa Maria Kabanjahe Private High School. Based on the results of the study, the posttest learning achievement value of the experimental class was 85.417 with a gain of 0.810, so it is included in the moderate category. While the learning achievement value of the control class was 77.083 with a gain of 0.709, so it is included in the high category. After being given treatment, the learning motivation value of the experimental class was 78.955 with a gain of 0.342, so it is included in the moderate category. These results correlate with learning motivation, with an r count of 0.794 and an r table of 0.349. In the control class it was 75.635 with a gain of 0.309, so it is included in the moderate category. Based on the results of the study, students who were taught using the Teams Games Tournament learning model with Interactive Wordwall media had better learning outcomes and motivation compared to students who were taught using the traditional method with Interactive Wordwall media. Keywords: Reaction Rate, Teams Games Tournament, Learning Outcomes, Learning                 Motivation, Wordwall